Quality of life in stroke patients at a hospital affiliated to Qom University of Medical Sciences - Ezzati, J; Karimi Rahjerdi, H; Nikravan Mofrad, M; Alavi Majd, H (Advances in Nursing & Midwifery, 2008)
Background Stroke is the first neurologic problem worldwide and the most common disabling neural disorder with severe complications threatening the life of patients and their families and affecting on their quality of life (QOL). Purpose This descriptive-correlational study was conducted to identify QOL of stroke patients referring to Kamkar-Arabnia Hospital affiliated to Qom University of Medical Sciences in 2002. Methods 70 stroke patients (27 Women and 43 men) between 40 and 90 with no history of chronic diseases and aphasia were selected by convenience sampling method. The patients suffered from the condition at least 2 months and at most 14 months (1-year duration). Data collection tools included a questionnaire in two parts: demographics and QOL domains. Results Mean age of the subjects was 63.7. Most patients considered their physical and psychological condition moderate but their socioeconomic condition weak. Conclusion Stroke lowers QOL in all physical, psychological, and socioeconomic domains. Therefore, it is suggested that health centers revise their plans to promote QOL while evaluating their therapeutic as well as supportive programs. Keywords: Quality of life (QOL), Stroke, Domains of QOL